Case Report: A Novel CXCR4 Mutation in a Chinese Child With Kawasaki Disease Causing WHIM Syndrome - Ma, Xiaopeng; Wang, Yaping; Wu, Peng; Kang, Meiyun; Hong, Yue; Xue, Yao; Chen, Chuqin; Li, Huimin; Fang, Yongjun (Frontiers in Immunology, 2022)
WHIM syndrome, an extremely rare congenital disease with combined immunodeficiency, is mainly caused by heterozygous gain-of-function mutation in the CXCR4 gene. There have been no previous case reports of WHIM syndrome with Kawasaki disease. We herein report a case of a boy who developed Kawasaki disease at the age of 1 year. After treatment, the number of neutrophils in his peripheral blood decreased continuously. His medical history revealed that he had been suffering from leukopenia, neutropenia and low immunoglobulin since birth, and his neutrophils could return to the normal level in the presence of infection or inflammation. Clinical targeted gene sequencing of 91 genes associated with granulocyte-related disease revealed that the patient had a novel heterozygous NM_003467; c.1032_1033delTG;p.(E345Vfs*12) variant in exon 2 of CXCR4 gene. Family verification analysis by Sanger sequencing showed that his father also had heterozygous variation at this site, while other family members did not. The computer prediction software indicated that the variation had a high pathogenicity. The computational structure analysis of the mutant revealed significant structural and functional changes in the CXCR4 protein. It should be noted that when unexplained persistent neutropenia with low immunoglobulin occurs after birth, especially when there is a family history of neutropenia, immunodeficiency should be investigated with genetic testing.